Atomic‐Scale Preparation of Octopod Nanoframes with High‐Index Facets as Highly Active and Stable Catalysts. Issue 8 (26th September 2016) - Luo, Shuiping; Tang, Min; Shen, Pei Kang; Ye, Siyu
Abstract : An atomic‐scale engineered octopod nanoframe architecture (OFA) consisting of 3D catalytic surfaces and beneficial high‐index facets is developed via a facile one‐pot synthesis method. Based on the reliable recipe and general method, various complex nanoframe architectures are developed. Specially, the PtCu OFAs exhibit exceptional activity and stability for the oxygen reduction reaction and can be easily scaled up to high‐quality.